Co‐occurrence of nonsuicidal self‐injury and eating disorder pathology in adolescents. Issue 2 (16th December 2022) - Reas, Deborah Lynn; Wisting, Line; Lindvall Dahlgren, Camilla
Abstract: Objective: Little is known about the co‐occurrence of nonsuicidal self‐injurious (NSSI) behaviors and eating disorder (ED) pathology in community samples of adolescents. Methods: A total of 1558 Norwegian upper secondary school students (Grades 11, 12, and 13) completed the Deliberate Self‐Harm Inventory and a measure of ED pathology. Results: Adolescents (53.1% F, 46.9% M) were a mean age of 17.1 years. A higher level of ED pathology was reported (12.1 vs. 5.3, p  < .001) among adolescents who had a history of NSSI. Significantly higher levels of ED pathology were found among females who reported hitting themselves until bruised, head banging, severe scratching, and burning with a lighter, but not cutting, or the other forms of self‐injury. Of adolescents with a history of NSSI, 60% of females and 15% of males scored above a cutoff for ED pathology. Of adolescents scoring above a cutoff for ED pathology, 42.5% of females and 37.1% of males had engaged in lifetime NSSI. Discussion: Adolescents—in particular, females— with a history of NSSI reported significantly greater ED pathology. Notably, a higher proportion of males with ED pathology reported lifetime self‐injury than vice versa, underscoring the importance of carefully screening for the presence of self‐harm among males with ED pathology. Public Significance Statement: Over 1500 upper secondary school students with an average age of 17 years completed an online survey assessing current ED pathology and lifetime NSSI. Adolescents, particularly females, with a history of self‐harm reported significantly more ED pathology. Findings also indicated the need to carefully screen for self‐harm among males with ED pathology. Parents, schools, and health professionals should be aware that self‐harm and ED pathology commonly co‐occur and warrant assessment.